The effectiveness of app‐based language instruction for developing receptive linguistic knowledge and oral communicative ability - Loewen, Shawn; Isbell, Daniel R.; Sporn, Zachary (Foreign language annals, 2020)
Hundreds of millions of language learners around the globe study a second language with popular apps such as Duolingo, Rosetta Stone, Busuu, and Babbel. This study examined the effectiveness of one app, Babbel, for developing both receptive linguistic knowledge of vocabulary and grammar, as well as oral communicative ability in Spanish as a second language. Fifty‐four English speakers not enrolled in Spanish classes studied Spanish on Babbel over the course of 12 weeks, with a goal of studying roughly 10 min per day. Participants completed pretests and posttests, and provided data on their motivation to learn Spanish and use Babbel. Results showed that learners were able to develop grammar and vocabulary knowledge as well as oral communicative ability. The amount of Babbel study time was the strongest predictor for all three measures, with motivation to learn Spanish also significantly predicting growth in oral communicative ability. The Challenge Hundreds of millions of learners use digital apps to learn world languages, but how effective are these apps for learning how to speak a second language? To answer this question, this article compares the grammar, vocabulary, and speaking development of 54 learners who spent three months studying Spanish with the app Babbel.